Pengaruh Perbandingan Terigu Dengan Tepung Kecambah Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Kue Lumpur - Abiburrahim, Abiburrahim; Wisaniyasa, Ni Wayan; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
The purpose of this study was to determine the effect of wheat flour comparison with red bean sprout flour on the characteristics of lumpur cakes and to determine the ratio of wheat flour to red bean sprouts flour which can produce mud cakes with the best characteristics.This research used a Completely Randomized Design (CRD) with a comparison of flour and red bean sprouts as treatment. Treatment consisting of 6 levels (100%: 0%, 80%: 20%, 60%: 40%, 40%: 60%, 20%: 80%, and 0%: 100%). The experimentation was repeated 3 times So that it is obtain 18 experimental units. Observed variables of moisture content, ash content, protein content, fat content, crude fiber content, color, aroma, taste, texture, and overall acceptance of lumpur cakes. The data obtained were then analyzed by variants and if there was any effect on the treatment, then continued with Duncan test. The results showed that the addition of red bean sprout affected moisture content, ash content, protein content, fat content, crude fiber content, color, aroma, taste, texture, and overall acceptance of lumpur cakes. The best characteristic of lumpur cake substitution was 60% wheat flour and 40% red bean sprouts flour that produced moisture content of 35,62%, an ash content of 0,78%, protein content of 11,09%, a fat content of 36,67%, crude fiber content of 16,47%, regular color (normal), aroma (like), soft texture (like), taste (like), and overall acceptance (like).